Keanekaragaman Jenis Fauna Endokarst Pada Beberapa Gua Di Kabupaten Maros dan Pangkep - Isa Wulandari; Mudatsir Zainuddin; Hamrullah Hamrullah; Muhammad Ruslan Umar; Ambeng Ambeng (Universitas Hasanuddin, 2023)
The cave ecosystem is a unique ecosystem that has many faunas with special adaptations to the extreme cave environment. Indonesia has many caves, which are scattered in the Maros-Pangkep area, South Sulawesi. This study aims to determine the diversity of fauna in six caves in the Maros-Pangkep area. The method used is the human mobile observation method with the sampling technique using direct collection techniques. The samples found were identified and analyzed for diversity using the Shannon-Wiener Diversity Index. The study results obtained 21 species of fauna that have been identified and 12 species that have not been identified. Almost all fauna are Arthropods with a dominance of the Insecta and Arachnida classes. The six caves have a diversity value between 1.57 – 2.20 which is classified as moderate diversity (1